Decision making based on Web 2.0 Data: The Small and Medium Hotel Management - Chaves, Marcirio (2012)
The decision-making process based on the user-generated content (UGC) can be used by several industries such as movies, books, tourism and hotels. This paper presents a fine-grained analysis of UGC for small and medium hotels (SMH). We collected and analysed 1500 online reviews from 50 SMH. This data was cross-referenced in order to find patterns that could support decision-making. The findings show that Room and Service were the concepts that guests pay more attention to in their review and ratings. For the concept Location, reviewers tend to value proximity of near trade centres and points of access to public transport. Tendencies to evaluate positively the hotels using high ratings were also identified. Although reviews receive high ratings, there is a significant number of negative considerations in these reviews. This paper also points the main features which SMH managers should prioritise according to the profile of the guest. For example, we found that British guests value tea- or coffee-making facilities in the room. This research concludes that online reviews provide useful information to help the SMH management in making decisions to increase customer satisfaction and to manage existing resources efficiently.